A Large Left Atrial Myxoma Obstructing the Mitral Valve Orifice - Hasan, Md Nazmul; Adhikary, Dipal Krishna; Parvin, Tanjima (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Cardiac tumors represent a relatively rare, yet challenging diagnosis. Secondary tumors are far more frequent than primary tumors of the heart. The majority of primary cardiac tumors are benign in origin, with primary malignant tumors accounting for 25% of cases. Left atrial myxoma is the most common intracardiac tumor. It could be seen in patients between 383 years of age, with the majority presenting in fifth decade of life as sporadic cases (90%) and second decade as familial cases (10%)1. It is an important source of central nervous system embolism2. Elderly patients often present with nonspecific symptoms that are often overlooked in the absence of a supporting cardiac history which makes an early diagnosis challenging. This case report discusses an unusual presentation of a large left atrial myxoma in a 35 years old patient which almost completely obstructing the mitral valve orifice during diastole. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i3.21043